Conditional deletion of Nedd4-2 in lung epithelial cells causes progressive pulmonary fibrosis in adult mice - Dürr, Julia; Leitz, Dominik; Szczygieł, Magdalena; Dvornikov, Dmytro; Fraumann, Simon; Kreutz, Clemens; Zadora, Piotr Kamil; Seyhan Agircan, Ayca; Konietzke, Philip; Engelmann, Theresa A.; Hegermann, Jan; Mulugeta, Surafel; et al. (Nature Communications, 2020)
Idiopathic pulmonary fibrosis (IPF) is a chronic progressive interstitial lung disease characterized by patchy scarring of the distal lung with limited therapeutic options and poor prognosis. Here, we show that conditional deletion of the ubiquitin ligase Nedd4-2 (Nedd4l) in lung epithelial cells in adult mice produces chronic lung disease sharing key features with IPF including progressive fibrosis and bronchiolization with increased expression of Muc5b in peripheral airways, honeycombing and characteristic alterations in the lung proteome. NEDD4-2 is implicated in the regulation of the epithelial Na+ channel critical for proper airway surface hydration and mucus clearance and the regulation of TGFβ signaling, which promotes fibrotic remodeling. Our data support a role of mucociliary dysfunction and aberrant epithelial pro-fibrotic response in the multifactorial disease pathogenesis. Further, treatment with the anti-fibrotic drug pirfenidone reduced pulmonary fibrosis in this model. This model may therefore aid studies of the pathogenesis and therapy of IPF.
Gesehen am 03.02.2025